BUILDING INFORMATION MODELING (BIM) CONTRIBUTION TOWARDS SUSTAINABILITY: AWARENESS OF MALAYSIAN CONTRACTORS - Sharifah Akmam, Syed Zakaria; Nur Soleha, Abdul Rahim (International Journal of Property Sciences (E-ISSN: 2229-8568), 2020)
Building Information Modelling (BIM) has become an attention-grabbing topic among researchers and industry players around the world including Malaysia. As the construction industry always plaguing with issues related to massive waste generated from construction and demolition process, encouraging BIM implementation is considered as one of the available technology-based alternatives to encounter these issues. BIM is a type of technology that offers the development of construction project before the real construction process, which allows the identification of any issues earlier, throughout the design and planning phases. Currently, numerous researches have been focusing on the benefits offered by BIM to the construction industry. However, there are still several construction players who lack awareness of BIM's contribution, especially towards sustainability. The purpose of this paper is to explore the awareness of contractors in Malaysia on the contribution of BIM towards sustainability, namely economic, environmental and social. A total of 133 contractors from grade G1 to G7 were involved in a survey. The results revealed that majority of the respondents were aware on BIM contributions towards environmental sustainability, besides other two sustainability pillars, economic and social. Thereby, there is a need to educate and provide realistic information to the construction industry stakeholders, as a process to create a better understanding and wider exposure, and to convince them to implement BIM technology.